Proposing a novel classification of growth periods based on biomechanical properties and seasonal changes of Spartina anglica - Keimer, Kara; Kosmalla, Viktoria; Prüter, Inga; Lojek, Oliver; Prinz, Markus; Schürenkamp, David; Freund, Holger; Goseberg, Nils (Frontiers in Marine Science, 2023)
Salt marshes are a valuable ecosystem with coastal protection potential, for example by absorbing hydrodynamic energy, increasing sedimentation and stabilizing the soil. This study investigated biomechanical properties of Spartina anglica to improve future models of wave-vegetation interaction. To fully understand the correlations between hydro- and biomechanics, the biomechanical vegetation properties from December 2021 to July 2022 are investigated with specimens collected from the field monthly. 551 specimens were used to determine the vegetation properties during storm surge season with high hydrodynamic forces. Additional geometrical properties were determined for 1265 specimens. Three-point bending tests measured the stiffness S (N/mm) and maximum forces Fmax (N). Different phenological states were observed over time and separated for analysis. These states provide a novel classification of growth periods for evaluating the coastal protection potential of Spartina anglica. Especially during storm season, most specimen were identified as broken shoots with a mean stiffness of 1.92N/mm (using 304 samples) compared to the bottom part of flowering shoots in December and January with a mean stiffness of 2.98N/mm (using 61 samples). The classification of plant properties recognizing phenological differences, based on plant state and seasonality, can be used to explain and reduce variability of biomechanical properties obtained during field campaigns. Additionally, this study shows that March to April is recommended for future investigations focusing on shoot properties during storm surge season, which is the important season for coastal engineers considering vegetation state.